Application of Computational Methods in Understanding Mutations in Mycobacterium tuberculosis Drug Resistance - Mugumbate, Grace; Nyathi, Brilliant; Zindoga, Albert; Munyuki, Gadzikano (Frontiers in Molecular Biosciences, 2021)
The emergence of drug-resistant strains of Mycobacterium tuberculosis (Mtb), impedes the End TB Strategy by the World Health Organisation aiming for zero deaths, disease, and suffering at the hands of tuberculosis (TB). Mutations within anti-TB drug targets play a major role in conferring drug resistance within the Mtb, hence computational methods and tools are being used to understand the mechanisms by which they facilitate drug-resistance. In this chapter, computational techniques such as molecular docking and molecular dynamics are applied to explore point mutations and their role in affecting binding affinities for anti TB drugs, often times lowering the protein’s affinity for the drug. Advances and adoption of computational techniques, chemoinformatics, and bioinformatics in molecular biosciences, resources supporting machine learning techniques are in abundance and this has seen a spike in its use to predict mutations in Mtb. This chapter highlights the importance of molecular modelling in deducing how point mutations in proteins confer resistance through destabilising binding sites of drugs effectively inhibiting the drug action.